The big deal about blades : laminar technologies and human evolution. - Bar-Yosef, Ofer (American Antropological Association, 1999)
Despite the rapid expansion of archaeological knowledge of the Paleolithic over the past several decades, some generalized interpretive frameworks inherited from previous generations of researchers are remarkably tenacious. One of the most persistent of these is the assumed correlation between blade technologies, Upper Paleolithic industries, and anatomically (and behaviorally) modern humans. In this paper, we review some of the evidence for the production of early blade technologies in Eurasia and Africa dating to the late Lower and the Middle Paleolithic. The basic techniques for blade production appeared thousands of years before the Upper Paleolithic, and there is no justification for linking blades per se to any particular aspect of hominid anatomy or to any major change in the behavioral capacities of hominids. It is true that blades came to dominate the archaeological records of western Eurasia and Africa after 40,000 years ago, perhaps as a consequence of increasing reliance on complex composite tools during the Upper Paleolithic. At the same time, evidence from other regions of the world demonstrates that evolutionary trends in Pleistocene Eurasia were historically contingent and not universal.